Design of Mobile-Based Samosir Tour Hero Tourism Application - Agnes Irene Silitonga (Geviva Publisher, 2025)
Samosir Tour Hero is an innovative platform designed to help tourists who want to explore Samosir Island easily, integrated, and informatively. The application offers detailed information on vehicle rentals, accommodations, and tourist destinations, and serves as a direct link between tourists and experienced local tour guides. With advanced features such as searching for nearby tourist locations, customized tour packages, and user reviews and recommendations, Samosir Tour Hero provides a comprehensive solution to enhance the tourist experience. The application has significant potential to boost the local economy, support tour guide activities, and strengthen the tourism sector in Samosir. With a user-friendly approach, simple yet effective interface design, and integration of transportation, accommodation, and tour guide services, Samosir Tour Hero aims to create a more personalized, comfortable, and memorable travel experience.